f(x) = [(e^x) - (e^-x)]/ (e^x)+(2^-x)]

= [(e^x)-(1/e^x)]/[(e^x)+(1/e^x)]

= (e^2x -1)/ (e^2x) +1)

= (e^2x +1 -2)/ (e^2x)+1)

= 1 -[2/(e^2x)+1]

y= 1- [2/(e^2x)+1)]

y-1= -2/(e^2x+1)

==> e^2x +1 = -2/(y-1)

==> e^2x = -2/(y-1) -1

==> 2x= ln [(-2/(y-1) -1]

= ln (-2-(y-1)/(y-1)

=...

## Unlock

This Answer NowStart your **48-hour free trial** to unlock this answer and thousands more. Enjoy eNotes ad-free and cancel anytime.

Already a member? Log in here.

f(x) = [(e^x) - (e^-x)]/ (e^x)+(2^-x)]

= [(e^x)-(1/e^x)]/[(e^x)+(1/e^x)]

= (e^2x -1)/ (e^2x) +1)

= (e^2x +1 -2)/ (e^2x)+1)

= 1 -[2/(e^2x)+1]

y= 1- [2/(e^2x)+1)]

y-1= -2/(e^2x+1)

==> e^2x +1 = -2/(y-1)

==> e^2x = -2/(y-1) -1

==> 2x= ln [(-2/(y-1) -1]

= ln (-2-(y-1)/(y-1)

= ln (-1-y)(y-1)

==> x=(1/2)*ln (-1-y)/(y-1)

The the inverse is:

f(x)^-1= (1/2)*ln [(-1-x)/(x-1)]